The Learning Module Uses FASTER Learning Model in C Programming Language Courses - Suryana, Febriyanno; Erdisna (Jurnal Pedagogi dan Pembelajaran, 2023)
The low ability of students in the C Programming Language course is due to the need for more use of models and media that suit student needs. This research aims to test the validity and practicality of the learning modules of the two model books: the lecturer's guidebook and the module book & student guide. This research belongs to the type of development research that was developed using the ADDIE model. Data collection used a questionnaire method and interviews with research instruments in the form of validity and practicality test instruments—data analysis techniques using qualitative and quantitative descriptive analysis. The data from the research analysis showed that the results of the expert assessment obtained an average value of 0.90 in the Valid category. Lecturer manual and the average value of 0.87. Module book & student guide with Valid category. The practicality of the lecturer's guidebook produces an average value of 90.09 (Very Practical). Practical module books & student guides produce an average value of 91.20 (Very Practical). It was concluded that the FASTER model is suitable for learning the C Programming Language, and the modules used are very easy to use and help in the learning process.